MRI Characterization of the Pore Structure Evolution by Forced Aeration during Heap Leaching. (September 2020) - Yu, Shaofeng; Gao, Pengju
Abstract: In spite of lots of methods in improving the performance of heap leaching, much controversy on the industrial applications remain. A relatively new and effective idea of introducing aeration to heap leaching, especially in abiotic heap leaching, may be a better way. Experiments on water content (WC) of the leaching columns employing a novel heap leaching apparatus and Magnetic Resonance Imaging (MRI) by changing aeration intensity (AI) were conducted. The results show that WC within the heap can be effectively increased which may enlarge the area of liquid-solid interface to probably improve the leaching efficiency and performance.